The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.35741/issn.0258-2724.54.5.28
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Slotted Block Horn Used For Ultrasonic Power Applications

Abstract: This research aims to contribute a study of design and simulate the ultrasonic block horn configuration containing two slots in order to satisfy these criteria. The simulation and vibration mode shape characterization for the selected horn profiles are discussed and the analysis is accomplished using ABAQUS commercial software package, whilst the vibration modes are classified using experimental data from 3D Laser Doppler Vibrometer measurements. Modal and harmonic analysis are completed successfully to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The displacement amplitude of both horns was measured using laser Doppler vibrometer and results were good in agreement with FEA results. Al Sarraf et al 14 designed and simulated the ultrasonic slotted block horn to optimize the slot positions using FEA. The FEA results showed that block horn with two slots improves the amplitude of vibration.…”
Section: Introductionmentioning
confidence: 99%
“…The displacement amplitude of both horns was measured using laser Doppler vibrometer and results were good in agreement with FEA results. Al Sarraf et al 14 designed and simulated the ultrasonic slotted block horn to optimize the slot positions using FEA. The FEA results showed that block horn with two slots improves the amplitude of vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic welding technique remain one of the major inescapable joining method, cost effective, robust and essential process that significantly apply on joining materials, polymers, composites and covered a wide range of manufacturing and industrial applications. The joining state of materials by ultrasonic is recognized through forming a solid-state condition at intimate surfaces without any fusion or melting (Lucas et al, 2008;Ziad Shakeeb Al Sarraf, 2019). Generally, ultrasonic welding system consist of driving piezoelectric transducer that convert the alternative current 50-60 Hz and raise up to 20 KHz or above by means the effect of piezoceramic discs, booster the second component which is optionally added to increase the amount of vibration amplitude delivering by transducer to the working area and to hold the welding rig securely and rigidly, while the last component which is described to be an essential component of welding system is a sonotrode or horn.…”
Section: Introductionmentioning
confidence: 99%